1999
DOI: 10.1016/s0014-5793(99)01667-1
|View full text |Cite
|
Sign up to set email alerts
|

Specific hydroxylations determine selective corticosteroid recognition by human glucocorticoid and mineralocorticoid receptors

Abstract: The ligand binding domains of the human mineralocorticoid receptor (hMR) and glucocorticoid receptor (hGR) display a high sequence homology. Aldosterone and cortisol, the major mineralocorticoid and glucocorticoid hormones, are very closely related, leading to the cross-binding of these hormones to both receptors. The present study reports on the mechanism by which hMR and hGR are activated preferentially by their cognate hormones. We found that the ability of corticosteroids to stimulate the receptor's transa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(142 citation statements)
references
References 27 publications
11
128
2
1
Order By: Relevance
“…2A). A similar observation was made by Hellal-Levy et al (47). This suggests, similar to cortisol, a partial antagonist effect of DOC at the hMR.…”
Section: Doc and Hmrsupporting
confidence: 86%
“…2A). A similar observation was made by Hellal-Levy et al (47). This suggests, similar to cortisol, a partial antagonist effect of DOC at the hMR.…”
Section: Doc and Hmrsupporting
confidence: 86%
“…One remarkable discrepancy is the MR binding affinity of cortisol being very close to that of aldosterone, while cortisol proved to be the weaker mineralocorticoid in terms of transactivation. Similar binding of aldosterone and cortisol to the hMR, but more potent transactivation via the MR by aldosterone, was described by Rupprecht et al (38) and Hellal-Lévy et al (43). The latter group showed that although the affinities for the MR are nearly the same, aldosterone dissociates much slower than cortisol from this receptor, and they assumed different induction of conformation changes of the MR by these ligands.…”
Section: -Ketosupporting
confidence: 64%
“…Second, the use of dexamethasone for glucocorticoid complementation prevented promiscuous activation of MR. Indeed, (1) because dexamethasone is approximately 100-fold more efficient than corticosterone for transactivating glucocorticoid receptors, 51 it could be administered at concentration of the same order as aldosterone, and (2) at this low concentration, even in the absence of 11␤-HSD2 activity, dexamethasone does not transactivate the MR because it is 1000-fold less efficient than aldosterone. 51 In summary, bile duct ligation in mice induces cirrhosis which, within 4-5 weeks, leads to the induction of Na ϩ ,K ϩ -ATPase in CCDs, to renal sodium retention and to ascites formation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, (1) because dexamethasone is approximately 100-fold more efficient than corticosterone for transactivating glucocorticoid receptors, 51 it could be administered at concentration of the same order as aldosterone, and (2) at this low concentration, even in the absence of 11␤-HSD2 activity, dexamethasone does not transactivate the MR because it is 1000-fold less efficient than aldosterone. 51 In summary, bile duct ligation in mice induces cirrhosis which, within 4-5 weeks, leads to the induction of Na ϩ ,K ϩ -ATPase in CCDs, to renal sodium retention and to ascites formation. Sodium retention, ascites formation and induction of Na ϩ ,K ϩ -ATPase are independent of the activation of mineralocorticoid receptors by either aldosterone or glucocorticoids, supporting the "overflow theory" of sodium retention in liver cirrhosis in the cholestatic mice model.…”
Section: Discussionmentioning
confidence: 99%